Stories Visitors Tell about Italian Cities as Destination Icons - Woodside, Arch; Cruickshank, B.; Dehuang, N. (Pergamon, 2007)
Using brand netnography (analyzing first-person on-line stories consumers tell that include discussions of their product and brand use), this article probes how visitors report specific Italian cities as unique brand icons. Visitor stories interpreting Bologna and Florence support Robert McKee's wisdom that powerful storytelling moves people via unique “inciting incidents”—incidents serving to unfreeze or throw life out-of-balance. The visitors’ city lived-dramas give credence to Tom Peter's advocacy of focusing strategically on brand experiences—“an experience–event–happening leaves an indelible memory” and Doug Holt's treatise on how brands become icons. The analysis includes applying Heider's balance theory in maps showing immediate and downstream positive and negative associations of concepts, events, and outcomes in visitors’ stories [cf. Collins, J., & Loftus, E. F. (1975). A spreading activation theory of semantic processing. Psychological Review, 87, 407–428; Epstein, S. (1994). Integration of the cognitive and the psychodynamic unconscious. American Psychologist, 49(8), 709–724]. These maps include descriptions of how visitors live Bologna's and Florence's unique promises (i.e., cultural beauty/decadence and total Italian Renaissance emersion, respectively). The article provides a revisionist proposal to Holt's five-step strategy for building destinations as iconic brands and suggestions for tourism management.